ANALISIS KEMAMPUAN AWAL LITERASI SAINS MAHASISWA PADA KONSEP IPA - Winata, Anggun; Cacik, Sri; R. W., Ifa Seftia (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2016)
Has conducted research that aims to determine the ability of early scientific literacy of students PGSD UNIROW on the concept of IPA consists of seven indicators: 1) identify the scientific opinion is valid 2) perform literature searches were effectively 3) to understand the elements of research design and how it will impact the findings / conclusions 4) make precise graph of the data; 5) solve problems using quantitative skills, including basic statistics; 6) understand and interpret basic statistics; 7) perform inference, prediction, and drawing conclusions based on quantitative data. The study is part of a study of the development of learning tools to improve science literacy. Science literacy proficiency tests were arranged were twenty-five items. Initial capability analyzed scientific literacy is the ability of scientific literacy of students before applied a model that could be expected to develop the ability of science literacy of students. The analysis showed that the literacy skills of students of higher science is an indicator of effective literature searches with a percentage of 40.15%. While the results of the analysis of the ability of scientific literacy of students lower is an indicator of solve problems using quantitative skills, including basic statistics with a percentage of 6.82%. The results obtained in accordance with the results of surve PISA 2003, 2006, 2009 and 2012 and the results of the TIMSS surve 2007dan year 2011 Indonesia demonstrate the ability of students in Indonesia, including in the low category.